Sediment stratigraphy in NYC salt marsh reveals extensive wetland loss, heavy metal pollution and blue carbon release - Goetz, Nathaniel; Chang, Clara; Kovari, Stephen; Alfano, Marina; Pal-Yadav, Aarna; Vaughn, Derrick; Peteet, Dorothy (Frontiers in Environmental Science, 2025)
Tidal wetlands provide critical ecosystem functions for coastal communities including flood protection, water filtration, carbon sequestration and aquatic nursery habitat. However, New York City’s salt marshes, including our study site at Pelham Bay Park’s Turtle Cove, are rapidly disappearing due to accelerating relative sea-level (RSL) rise and coastal development. Field research, mapping and satellite imagery reveal significant loss of this ∼10 hectare (ha) wetland, as perturbations from human activity prevent marsh landward migration, impede tidal flows and threaten marsh survival. We extracted three sediment cores and conducted 20 m transects across a gradient of disturbed marsh areas. We present the analyses of land-use change, X-ray fluorescence (XRF), loss on ignition (LOI), stable carbon isotopes (δ13C), foraminifera, and accelerator mass spectrometry (AMS) radiocarbon dating of terrestrial macrofossils to examine the past and to inform future conditions for this rapidly eroding wetland. Moreover, we reconstruct sea level over a millennium to analyze changes in marsh plant communities in response to RSL rise and coastal development. We found that between 1974 and 2018 CE, ∼65% of marsh disappeared at a rate of 1.5% yr-1 or 800 m2 yr-1. The marsh loss coincided with increasing RSL rates of 3.5 mm yr-1 from 1958-1975 CE to 6.7 mm yr-1 from 1999-2024 CE. Meanwhile, developed areas expanded 568 m2 yr-1 from 1985-2023 CE, replacing wetland areas and disrupting hydrologic processes with hardened shorelines. Marsh loss resulted in the release of soil organic carbon stored over many centuries and a concerning amount of lead (Pb) into Long Island Sound, presenting risks to public health and wildlife. Culvert assessments demonstrated that tidal restriction by built structures contributed to rising tide levels comparable to RSL rise over the past century, which likely exacerbated marsh erosion. Lastly, tidal prism reductions caused enough accumulation of heavy metals to significantly alter peat chemical composition for a century. This study improves our understanding of compounded stressors that prevent the capacity of salt marshes to with stand anthropogenic impacts. Ultimately, our findings inform an adaptive management of these threatened ecosystems in their struggle to keep pace with climate change and urbanization.